Is Current Research Assisting the Implementation of Contemporary ICT in the Primary Mathematics Classroom? - Catherine Attard (Southeast Asian Mathematics Education Journal, 2016)
The fast pace of development of ICT often results in primary teachers being expected to integrate new technologies effectively prior to the emergence of research findings that provide exemplars of best practice. This discussion paper explores contemporary research into ICT and primary school mathematics, and the issues that arise in relation to mobile technologies such as computer tablets in primary school classrooms. Although studies are beginning to emerge, this paper presents the argument that further research that would assist teachers in being prepared to teach mathematics with any technological tool would be more beneficial than working retrospectively to explore the use of specific devices that have already emerged in primary classrooms.